2022
DOI: 10.4103/sjmms.sjmms_306_20
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Dental Trauma Management among School Teachers in Dammam, Saudi Arabia

Abstract: Background: Children and young adolescents commonly suffer traumatic dental injuries. Teachers are frequently first responders and responsible for the initial management of the injury; the prognosis of a traumatized tooth is dependent on the initial management. Aim: To evaluate intermediate school teachers’ level of knowledge and attitudes toward dental trauma. Materials and Methods: This is a questionnaire-based cross-sectional study where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…These include epileptic episodes, diabetes, asthma attacks, sudden cardiac death, and others. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include epileptic episodes, diabetes, asthma attacks, sudden cardiac death, and others. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] To prevent these consequences, other researchers in India demonstrated that proper training in first aid for schoolteachers resulted in an enormous improvement in the teachers’ knowledge of paediatric first aid. [ 8 ] However, most of these studies were carried out in different environments than in Saudi Arabia, which necessitates the importance for us to carry out this study.…”
Section: Introductionmentioning
confidence: 99%
“…2,9,24,31 Ülkemizde ve diğer ülkelerde yürütülen benzer çalışmalarda, ilk yardım eğitimi alan öğretmenlerin sayısının düşük olduğu ve bu eğitimlerin çoğunun diş yaralanmalarını kapsamadığı bildirilmiştir. 31,32 Diş yaralanmaları hakkında eğitim almış öğretmenlerin ise bu süreci daha doğru yönetebilecekleri belirtilmiştir. 9,13,28,30,31,33 Çalışmamızda da benzer şekilde daha önce diş yaralanmaları hakkında eğitim almış öğretmenlerin oranının düşük olduğu (%6,2) ve eğitim almamış öğretmenlere kıyasla doğru cevap oranlarının daha yüksek olduğu tespit edilmiştir.…”
Section: Discussionunclassified
“…13,28,33 Bu sonuçlar doğrultusunda, diş yaralanmaları hakkındaki ilk yardım bilgilerinin öğretmenlerin eğitim programlarına eklenmesi veya farklı kaynaklar aracılığı ile güncel tutulmasının, öğretmenlerin acil durumlar karşısında daha başarılı davranışlar sergilemesi bakımından önemli olduğu düşünülmektedir. 32,34 Çalışmamızda öğretmenlerin yaklaşık yarısı daha önce bir diş yaralanmasına şahit olmuş olup, verdikleri doğru cevap oranı daha yüksek bulunmuştur. Benzer bir çalışmada diş yaralanmasına şahit olan öğretmenlerin, avulsiyon yaralanmalarını 2,3 kat daha doğru yönetebilecekleri gösterilmiştir.…”
Section: Discussionunclassified
“… 25% Al-Qahtani et al (2019) 36 Arar 20–50 M/F 404 Epilepsy Not reported Bachelor: 75% Master: 9.7% Diploma: 14.6% Experience: >10 y: 43% 5–10 y: 23.8% ≤5 y: 30.2% 0% Cross-sectional Teachers’ knowledge and practices regarding epilepsy management were poor. 75% Al-Khalifa and AlYousef (2022) 35 Dammam Not reported M/F 398 Dental emergencies Intermediate Experience: Mean±SD: 9.11±5.8 y Range: 1–32 y 30% Cross-sectional Teachers’ knowledge about dental emergencies and their management was poor. They were eager to attend first-aid training.…”
Section: Methodsmentioning
confidence: 99%